Hematocrito, Hemoglobina, Indices Eritrocitarios y Hierro Sérico como parámetros en la ayuda Diagnóstica y preventiva de Anemia Ferropénica en los niños del Barrio Pasallal - Cantón Calvas. - Ambuludí, Danixa (2013)
Iron deficiency is the most common cause of anemia in childhood and the most widespread nutritional deficiency in the world. Children are particularly susceptible because of their rapid growth and the limitation of their iron stores . In the Province of Loja in 2010 , rates of anemia was 64.1% in children under 5 years. The Neighborhood Pasallal , where the research was conducted , does not have adequate sanitary toilet infrastructure , they have quick and easy access to health facilities and are not sufficiently addressed by authorities to ensure their welfare. This study set out to determine the percentage of hematocrit and hemoglobin and red cell indices and serum iron by applying manual and colorimetric method , linking iron levels with haematological parameters obtained with the aim of contributing to the presumptive diagnosis of iron deficiency anemia. This descriptive research included 62 children who met the inclusion criteria , for which informed consent was obtained , with the results reached the following conclusions : 31 % of children / as presented values ​​of hematocrit, hemoglobin and decreased red cell indices , 35 % had decreased serum iron values ​​and establishing a relationship between serum iron values ​​obtained with haematological values ​​was found that 31% of the study population are within a presumptive diagnosis of iron deficiency anemia and finally spread the results, the doctor of Health Sub - center of the parish Sanguillín , which were helpful for diagnosis and treatment of infants investigated. Keywords: Hematocrit , hemoglobin , red cell indices , serum iron , iron deficiency anemia, children / as .